On the construction of asymptotic approximations for a nonautonomous wave equation - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For a nonautonomous wave equation with homogeneous boundary conditions, we construct one-frequency approximations of asymptotic solutions by using periodic Ateb-functions. Resonance and nonresonance cases are considered.